An Account of the Excavation of a Cairn and of the Remains of Four other Cairns in the Parish of Muirkirk, Ayrshire, and the Discovery of a Deposit of Burnt Human Bones at Borland, Old Cumnock, Ayrshire - Fairbairn, Archibald (Proceedings of the Society of Antiquaries of Scotland, 1922)
A circular cairn at Linburn Plantation covered a central circle of stones around a pit containing burnt bone, charcoal and two flint knives. There was evidence of in situ burning. Four round cairns in the parish of Muirkirk were examined. Only one had a central cist. Pottery, charcoal and a flint flake were recovered. An isolated deposit of burnt bone may have been associated with a cinerary urn found there in 1899.